The Implementation of Intellectual Property Registration for Startups in the Industrial Revolution Era 4.0 in Pontianak - Tri Atika Febriany; Heru Yudi Kurniawan; Deni Setiyawan (Indonesia Law Reform Journal, 2022)
The development of thinking supported by the ease of obtaining information in real-time with the assistance of a smartphone has changed a person’s pattern of life and the way to socialize. With the current technology, face-to-face socialization has been shifted to video calls. Not only socializing patterns, trading patterns have also been affected. Today trading process is not only held conventionally (buyers come to the store), but also by using the available applications. Through the applications, we can buy goods without having to leave the house. The presence of this change cannot be separated from the role of technology-based startups which create an application offering a variety of convenience services. The growth of the nation’s startups has now penetrated the world market. Some Indonesian startups have a valuation of US $ 1 billion and are included in the Unicorn class such as Tokopedia, Buka Lapak, and Traveloka. Now Go-Jek has also entered the Decacorn class. To protect their business, businessmen need to register their brands for intellectual property. Considering the importance of intellectual property in the industrial revolution 4.0, the researchers carried out this research to protect digital startups in Pontianak, especially in terms of intellectual property registration.